1982
DOI: 10.2134/agronj1982.00021962007400010027x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Grain Yield and Nutrient Response to Foliar Fertilizer Applied during Grain Fill1

Abstract: Recently there has been renewed interest in foliar fertilization of field crops, but little work with foliar application of nutrients on corn (Zea mays L.) during the grain filling period has been reported. This study was conducted to observe the effect of foliar fertilizer on corn grain yield, yield components, and nutrient content in the grain at harvest, while plants were subjected to moisture stress imposed after silking in one, two, or three successive stress periods. Experiments were conducted in the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…The difference in dry matter distribution was associated with differences in weather conditions between the 2 yr. In accordance with this result, previous studies also showed that foliar N spray affected neither the yield nor the stover dry matter of maize compared with the equivalent N applied to the soil (Harder et al 1982a;Below et al 1984a).…”
Section: Grain Yield and Stover Dry Mattersupporting
confidence: 69%
See 2 more Smart Citations
“…The difference in dry matter distribution was associated with differences in weather conditions between the 2 yr. In accordance with this result, previous studies also showed that foliar N spray affected neither the yield nor the stover dry matter of maize compared with the equivalent N applied to the soil (Harder et al 1982a;Below et al 1984a).…”
Section: Grain Yield and Stover Dry Mattersupporting
confidence: 69%
“…In previous studies, foliar N spray did not consistently increase yield (Harder et al 1982a;Below et al 1984a,b). It was reported that foliar fertilization for winter wheat did not affect grain yield (Woolfolk et al 2002).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…One consistent result of the study was that all foliar-applied P treatments achieved higher concentrations than the check. In their study, Harder, Carlson, and Shaw (1982) found that percent P in grain was increased by 230 mg kg 21 (4.7% increases) by foliar fertilization compared with the control. However, their analysis did not detect significant differences within foliar P rates.…”
Section: Grain and Forage P Concentrationmentioning
confidence: 93%
“…Harder, Carlson, and Shaw (1982) found that foliar fertilizer applied after silking did not translate into increased grain yield. On the other hand, Barel and Black (1979b) reported an increased grain yield due to foliar P compared with control (untreated check).…”
Section: Grain and Forage Yieldsmentioning
confidence: 95%